Ambient Air Pollution-related Mortality in Dairy Cattle: Does It Corroborate Human Findings?. Issue 6 (November 2016) - Cox, Bianca; Gasparrini, Antonio; Catry, Boudewijn; Fierens, Frans; Vangronsveld, Jaco; Nawrot, Tim S.
Abstract : Background: Despite insights for humans, short-term associations of air pollution with mortality to our knowledge have never been studied in animals. We investigated the association between ambient air pollution and risk of mortality in dairy cows and assessed effect modification by season. Methods: We collected ozone (O3 ), particulate matter (PM10 ), and nitrogen dioxide (NO2 ) concentrations at the municipality level for 87, 108 dairy cow deaths in Belgium from 2006 to 2009. We combined a case-crossover design with time-varying distributed lag models. Results: We found acute and delayed associations between air pollution and dairy cattle mortality during the warm season. The increase in mortality for a 10 μg/m 3 increase in 2-day (lag 0–1) O3 was 1.2% (95% confidence interval [CI] = 0.3%, 2.1%), and the corresponding estimates for a 10 μg/m 3 increase in same-day (lag 0) PM10 and NO2 were 1.6% (95% CI = 0.0%, 3.1%) and 9.2% (95% CI = 6.3%, 12%), respectively. Compared with the acute increases, the cumulative 26-day (lag 0–25) estimates were considerably larger for O3 (3.0%; 95% CI = 0.2%, 6.0%) and PM10 (3.2%; 95% CI = −0.6%, 7.2%), but not for NO2 (1.4%; 95% CI = −4.9%, 8.2%). In the cold season, we only observed increased mortality risks associated with same-day (lag 0) exposure to NO2 (1.4%; 95% CI = −0.1%, 3.1%) and with 26-day (lag 0–25) exposure to O3 (4.6%; 95% CI = 2.2%, 7.0%). Conclusions: Our study adds to the epidemiologic findings in humans and reinforces the evidence on the plausibility of causal effects. Furthermore, our results indicate that air pollution associations go beyond short-term mortality displacement. (See video abstract athttp://links.lww.com/EDE/B105 .) Abstract : Supplemental Digital Content is available in the text.